2010
DOI: 10.1109/memb.2010.936454
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Analysis for Intensive Care: Development and Deployment of the Artemis Analytic System

Abstract: The lives of many thousands of children born premature or ill at term around the world have been saved by those who work within neonatal intensive care units (NICUs). Modern-day neonatologists, together with nursing staff and other specialists within this domain, enjoy modern technologies for activities such as financial transactions, online purchasing, music, and video on demand. Yet, when they move into their workspace, in many cases, they are supported by nearly the same technology they used 20 years ago. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(70 citation statements)
references
References 12 publications
0
69
0
1
Order By: Relevance
“…Note that this work still relies on laboratory results and thus is not being directed towards an earlier detection of the infection. The Artemis system [12], a stream computing project for neonatal intensive care, sets the detection of sepsis as one of its primary objectives. Their method introduces patient agents (PAs) able to perform multi-dimensional temporal abstraction on monitoring data [13].…”
Section: Introductionmentioning
confidence: 99%
“…Note that this work still relies on laboratory results and thus is not being directed towards an earlier detection of the infection. The Artemis system [12], a stream computing project for neonatal intensive care, sets the detection of sepsis as one of its primary objectives. Their method introduces patient agents (PAs) able to perform multi-dimensional temporal abstraction on monitoring data [13].…”
Section: Introductionmentioning
confidence: 99%
“…Иными словами, области трансляционной биоин-форматики отведена роль «мостика» между знаниями фундаментальных исследователей и врачей-клини-цистов, чтобы «принести инновации с лабораторно-го стола к постели пациента» («link innovations from bench to bedside») [51,52]. В частности, в Госпитале для больных детей (The Hospital for Sick Children) в Торонто (Канада) был осуществлен пилотный проект анализа жизненных показателей в режиме реального времени [53], а в другой работе было про-демонстрировано, что паттерны данных жизненных показателей могут помочь прогнозировать как кратко-срочную, так и долгосрочную заболеваемость у недо-ношенных детей [54].…”
Section: персонализированная педиатрияunclassified
“…The concept of correlating such readings and even feeding these to a predictive mathematical model, is an active research topic in clinical medicine. Earlier research [21] showed the viability of physiological monitoring to detect sleep apnea in neo-natal ICU. NanoStreams extends the concept of utilising real time data to address the challenges of improving the standard of care by using a rapidly responsive automated surveillance system in an adult ICU.…”
Section: Real-time Computation In Diagnostic Medicinementioning
confidence: 99%